RELASI KUASA DALAM WACANA BERPEGANG TEGUH KEPADA DUA PUSAKA PENINGGALAN RASULULLAH (HADIS TSAQALAIN) DI INDONESIA - Hartono, Heki (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2019)
The article explor ideological, normative and scientific hadith as well as the power relation and its contestation that contribute to the perpetuation of the hegemony of back to the Qur’an and Sunna discourse. It also discloses the mechanism of knowledge power that operates in the discourse of the issue. The phenomenon of back to the Qur’an and Sunna illustrates how knowledge is constructed, controlled and perpetuated through several mechanisms to be eventually systematic discursive practice. Norm and social order which operate in the system of power as the ruler and controller of the the practice and the continuation of the power of the knowledge. A set of norms and orders including the banning, compulsory, stigmatization, and stereotype become strategic mechanism in strengthening the knowledge power on back to the Qur’an and Sunna. Several religious and cultural practices become the locus to instill the norms. All the reconstruction become strategic mechanism to hegemony public understanding.Keywords : Qur’an; Holy book; Hadith; Ahlul Bait; Power Relation